Variabilidade espaço-temporal da precipitação do Alto São Francisco (sub-40) utilizando dados do sensor PR/TRMM - Passos, Jacqueline Sobral de Araújo (2015)
The precipitation, due to its importance, is considered one of the main variables of the hydrological cycle. An alternative to collect rainfall data is using rainfall measurements by sensors/satellites. Among these kinds of alternative, the Tropical Rainfall Measuring Mission (TRMM) allows the collection with a spatial resolution 0.25º × 0.25º. Thus, the objective of the study is to understand, in more detail, the behavior and distribution of rainfall throughout the Upper São Francisco basin (Sub-40), in a recent period (1998-2013). The survey was conducted in the following steps: collection of TRMM rainfall data from 1998 to 2013 organizing them monthly and yearly; getting Três Marias reservoir in flow data; getting altimetry SRTM data; analyzing the correlation between the TRMM precipitation and the inflows to Três Marias reservoir; generating surface profiles to compare with the precipitation data, analyzing the number of consecutive dry days and consecutive wet days; computing the Standardized Precipitation Index - SPI for each point (169 points); spatial distribution of annual and monthly accumulated rainfall data, the correlation of rainfall and flow, of consecutive wet and dry days, the SPI index and cluster analysis. According to the results, it can be concluded that the years of highest and lowest value of annual rainfall depth was respectively 2009 and 2012. The driest months are June to August, and July is the driest one. In contrast, the wettest months are from November to January, and most rainy month is December. The annual and monthly precipitation depth showed that the northeast region of the basin rains less and the western and southern basin are wetter. The precipitation response to the inflow to the Três Marias reservoir is four days after the rainfall occurs. The relation between precipitation and altimetry shows that most of the annual rainfall depth is directly proportional to altimetry, but in some cases it shows little variability in the ground. Regarding the SPI, it was possible to calculate the beginning, end, intensity and magnitude of each dry and wet season. From the maps, SPI spatial information was produced in order to identify for each period the regions with highest and lowest values. By means of the map and dendrogram clusters, regions with higher and lower similarity between the monthly accumulated rainfall data were identified. Finally, the TRMM sensor proved useful in the analysis of spatial and temporal variability of precipitation over the studied basin, accounting satisfactorily dry and rainy periods. With easy acquisition and handling, satellite data is a viable alternative to collect precipitation data with spatial and temporal quality, especially in areas of difficult access or in developing countries.